2002
DOI: 10.1002/jcb.10227
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of protein kinase C‐α binding to lamin A

Abstract: Previous results from our laboratory have identified lamin A as a protein kinase C (PKC)-binding protein. Here, we have identified the regions of PKC-alpha that are crucial for this binding. By means of overlay assays and fusion proteins made of glutathione-S-transferase (GST) fused to elements of rat PKC-alpha, we have established that binding occurs through both the V5 region and a portion of the C2 region (i.e., the calcium-dependent lipid binding (CaLB) domain) of the kinase. In particular, we have found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…Alternatively, it may also protect binding sites for stress-relevant partners that interact with the lamin A tail. These include SREBP (Lloyd et al, 2002), PKCa (Tang et al, 2000), 12(5)-lipoxygenase (Martelli et al, 2002), c-fos (Ivorra et al, 2006) and ERK (Gonzalez et al,2008). Indeed, our observation that some of the single mutants (C522A and C588A) promote multiple intermolecular interactions supports the notion that the conserved cysteine residues form cross-linkages with several different proteins.…”
Section: Cysteine Modifications and Cellular Agingsupporting
confidence: 79%
“…Alternatively, it may also protect binding sites for stress-relevant partners that interact with the lamin A tail. These include SREBP (Lloyd et al, 2002), PKCa (Tang et al, 2000), 12(5)-lipoxygenase (Martelli et al, 2002), c-fos (Ivorra et al, 2006) and ERK (Gonzalez et al,2008). Indeed, our observation that some of the single mutants (C522A and C588A) promote multiple intermolecular interactions supports the notion that the conserved cysteine residues form cross-linkages with several different proteins.…”
Section: Cysteine Modifications and Cellular Agingsupporting
confidence: 79%
“…To determine whether PLC␤ was involved in nuclear mGlu5-mediated Ca 2ϩ responses, siRNA targeted against PLC␤1, the most prevalent nuclear isoform (41), was used to knockdown expression. Western blotting of striatal lysates prepared 48 and 72 h after siRNA transfection showed that there was at least a 60 -70% knockdown of PLC␤1 using the targeted siRNA versus a scrambled control (Fig.…”
Section: Mglu5 Receptors Are Localized At Both the Plasma Andmentioning
confidence: 99%
“…Three signaling proteins are known to bind A-type lamins in vivo; lamin filaments might therefore provide a structural basis for signaling. Protein kinase C α (PKCα) -a serine-threonine kinase activated by many signals, including diacylglycerol (DAG) and 12(S)-hydroxyeicosatetraenoic acid [12(S)-HETE] -binds to the C-terminal half of the lamin A/C tail (Martelli et al, 2002) (Fig. 1).…”
Section: Signaling Partnersmentioning
confidence: 99%